Determination of systemic inflamatory biomarkers in multiple sclerosis - Todorović, Maša; Nikolić, Stanislava; Živanović, Željko; Simić, Svetlana; Sakalaš, Lorand; Spasić, Igor; Ilinčić, Branislava; Čabarkapa, Velibor (Journal of Medical Biochemistry, 2023)
Background: Multiple sclerosis is one of the most common demyelinating diseases of the central nervous system. We aimed to investigate serum and cerebrospinal fluid levels of different laboratory inflammatory biomarkers in patients with MS. Methods: A total of 120 subjects participated in the study, 60 of whom are diagnosed with MS, 30 with the final diagnose of non-inflammatory diseases of the CNS, and 30 healthy subjects representing the control group. Regarding to progression of radiological findings after 2 years from the initial diagnosis, MS group was divided into subgroups: with stationary radiological findings (n=30) and with radiologically proven disease progression (n=30). In all patients we analyzed levels of laboratory inflammatory biomarkers: CRP, NLR, GDF15 and NFs. Values of NFs and GDF15 were analyzed initial while the values of CRP and NLR were analyzed initial and after two years. Results: We found statistically lower GDF15 values and initial CRP values in MS group in regards to group with non-inflammatory diseases of the CNS (p=0.000). On the other side, we determined significant elevation of laboratory markers CRP and NLR, initial and after two years period, in MS subgroup with progression of MRI findings (p= 0.000 and p=0.050, respectively). Also we found a positive correlation of CRP and neurofilaments (r=0.243, p=0.04), as well as a positive correlation of CRP and GDF15 in patients with MS (r=0.769, p=0.000). Conclusion: We found significant elevation of laboratory markers of systemic inflammation, CRP and NLR in MS patients who developed disease progression based on MRI findings. Key words: Multiple sclerosis; Neutrophil to lymphocyte ratio; C reactive protein, Neurofilaments, Growth differentiation factor 15